Prognostic factor of lower limb amputation among diabetic foot ulcer patient in Kelantan from 2014 to 2018 - Rosedi, Anas (2021)
Background: Lower Limb Amputation (LLA) was a common complication of Diabetic Foot Ulcer (DFU). It was a serious problem as it may lead to a reduction in patient's survival. However, knowledge on the prognostic factor of LLA was still scarce and require further exploration. Objectives: To determine the median amputation-free time among DFU patient and the prognostic factor of LLA among DFU patient in Kelantan from 2014 till 2018. Methodology: A retrospective study was conducted in October 2020 using secondary data obtained from National Diabetic Registry (NDR). The cohort consisted of data accrued from January 1st, 2014, till December 31st, 2018. The cohort was then followed up till December 31st, 2019. Three hundred sixty-two cases that fulfilled the study criteria were analysed further. Amputation-free time was determined using Kaplan Meier Method. The prognostic factors were determined by univariate and multivariate analysis using the Cox Regression Proportional Hazard. Result: Descriptive statistics showed that this cohort had a mean (SD) age of 59.0 (10.0) years old. Female patient consisted of 61.6%, which made the ratio of male to female is 1: 1.6. Patient with Obese BMI consisted of 55.9% of the sample. Patient with normal HDL- Cholesterol level consisted of 37.3% of the sample. The majority of the sample (92.8%) were non -smoker. There were 66 (18.2%) DFU patient who had LLA in this study. At the same time, 296 (81.8%) did not undergo LLA or died before LLA. Due to insufficient event of LLA, only mean amputation-free time was determined, which was 59.35 month (95% CI: 56.63, 62.08). The result of Cox Proportional Hazard Regression revealed three significant findings. Patient with DFU aged 60 or more had 52% lesser risk to LLA compared to DFU patient aged less than 60 (Adj. HR 0.48; 95% CI: 0.27, 0.89; p-value = 0.019). Patients with DFU who was obese had a 55% lesser risk of LLA than patients with DFU who had normal BMI (Adj. HR 0.45; 95% CI: 0.22, 0.89; p-value = 0.039). Patients with abnormal HDL-Cholesterol had a 2.18 times higher risk to LLA than patients with normal HDL-Cholesterol levels (Adj. HR 2.18; 95% CI: 1.21, 3.92; p-value = 0.009). Conclusion: The result on prognostic factor analysis opened a new horizon for future study, and it also assisted in intervention planning for DFU patient to prevent them from LLA.